Effectiveness and safety of Lacosamide therapy for children with focal epilepsy: a real world study - Yang, Chunsong; Liu, Zheng; Peng, Yuxuan; Zhang, Lingli; Yu, Dan (Frontiers in Pharmacology, 2023)
Objectives: To compare the effectiveness and safety of the new antiepileptic drug, lacosamide (LCM) with Levetiracetam, for the treatment of focal epilepsy in children.This study was a cohort study. Children with focal epilepsy who received LCM or Levetiracetam treatment in West China Second Hospital of Sichuan University were recruited and followed up for 12 months. Changes in the frequency of epilepsy, 50% and 75% responder rates, and seizure freedom rates from baseline to the maintenance period and adherence score were assessed. In addition, adverse events (AEs) were recorded.Results: 92 patients completed the study, and were divided into two groups: LCM (n=46) and Levetiracetam (n = 46). Participants were aged from 2 to 16.3 years, with a mean epilepsy duration of 2.57 years. The average maintenance dose of LCM was 5.03±1.91 mg/kg/d after the titration period.There was no significant difference between the two groups in terms of the mean seizure frequency during subsequent visits at 1, 3,6, 9, 12 months. There was significant difference between the two groups in terms of the 50% responder rate at 6 months. No serious AEs were reported in both groups.The vast majority of patients had good adherence (adherence score=4) in the LCM group.LCM is effective as adjunctive therapy in children with epilepsy and has good safety, tolerability and adherence. Large sample size studies with long-term follow-up are needed in the future to comprehensively evaluate the use of LCM in children.